Does Democracy Still Fall? A Bibliometric Analysis Two Decade 2004-2024 - Fernando, Henky; Larasati, Yuniar Galuh; Wuysang, Julia Magdalena; Hakim, Putri Rahmah Nur; Cahyani, Novita (Fenomena, 2024)
This study aims to explore and evaluate studies that have addressed issues of democratic failure in the last two decades, 2004-2024. In addition to using bibliometric analysis, this study also uses VOSviewer application-based software in exploring and evaluating entity patterns, themes, and developments of studies that focus on discussing democratic failure in the last two decades, 2004-2024. From exploring 1063 total documents, this study found that the United States, the United Kingdom, and the Russian Federation are the most active in publishing studies focusing on democratic failure in Democratization Journal, Journal of Democracy, Political Quarterly, and Third World Quarterly. However, these studies have not been able to intervene and respond to the structural, cultural, and even spiritual challenges that underlie the difficulty of implementing a democratic political system in the era of globalization. This study also recommends the importance of future studies to analyze the factors and implications of the failure of democracy in concept and practice on the welfare of the people in a country. Penelitian ini bertujuan untuk mengeksplorasi dan mengevaluasi studi-studi yang membahas isu-isu kegagalan demokrasi dalam dua dekade terakhir, 2004-2024. Selain menggunakan analisis bibliometrik, studi ini juga menggunakan perangkat lunak berbasis aplikasi VOSviewer dalam mengeksplorasi dan mengevaluasi pola entitas, tema, dan perkembangan studi yang fokus membahas kegagalan demokrasi dalam dua dekade terakhir, 2004-2024. Dari penelusuran terhadap 1063 total dokumen, studi ini menemukan bahwa Amerika Serikat, Inggris, dan Federasi Rusia merupakan negara yang paling aktif dalam mempublikasikan studi yang fokus membahas mengenai kegagalan demokrasi di Jurnal Demokrasi, Jurnal Demokrasi, Political Quarterly, dan Third World Quarterly. Namun demikian, studi-studi tersebut belum mampu mengintervensi dan menjawab tantangan-tantangan struktural, kultural, bahkan spiritual yang mendasari sulitnya penerapan sistem politik demokratis di era globalisasi. Penelitian ini juga merekomendasikan pentingnya penelitian-penelitian di masa depan untuk menganalisis faktor-faktor dan implikasi dari kegagalan demokrasi secara konsep dan praktik terhadap kesejahteraan rakyat di suatu negara.